A Beginner's Guide to Begonias: Begonia rex-cultorum - Julian Ginori; Heqiang Huo; Dave Norman (EDIS, 2022)
Rex begonias are spectacular rhizomatous perennials famous for their variegated, colorful foliage and ease of growth. Rex begonias are well suited for hanging baskets, windowsills, or houseplants. In more tropical climates, like Florida, rex begonias can also be found adding vibrant foliage and dimension to landscapes. This new 3-page publication of the UF/IFAS Environmental Horticulture Department is meant for Florida homeowners and horticulturalists interested in learning more about begonias. https://edis.ifas.ufl.edu/ep632